Identification of common molecular signatures of SARS-CoV-2 infection and its influence on acute kidney injury and chronic kidney disease - Zhang, Weiwei; Liu, Leping; Xiao, Xiangcheng; Zhou, Hongshan; Peng, Zhangzhe; Wang, Wei; Huang, Ling; Xie, Yanyun; Xu, Hui; Tao, Lijian; Nie, Wannian; Yuan, Xiangning; et al. (Frontiers in Immunology, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the main cause of COVID-19, which has resulted in hundreds of millions of confirmed cases and more than 18.2 million deaths worldwide. Acute kidney injury (AKI) is a common complication of COVID-19 that leads to an increase in mortality in infected patients, especially in ICU settings, while patients with chronic kidney disease (CKD) are at high risk for SARS-CoV-2 infection and related mortality. However, the underlying molecular mechanisms among AKI, CKD and COVID-19 are not unclear. Therefore, transcriptome analysis was performed to examine common pathways and molecular biomarkers for AKI, CKD and COVID-19, which help understand the association of SARS-CoV-2 infection with AKI and CKD. In this paper, we employed three RNA-seq datasets (GSE147507, GSE1563 and GSE66494) from the GEO database to detect differentially expressed genes (DEGs) among COVID-19 with AKI and CKD to search for shared pathways and candidate targets. A total of 17 common DEGs among these datasets were confirmed, and their biological functions and signaling pathways were characterized by enrichment analysis. MAPK signaling, the structural pathway of interleukin 1 (IL-1) and the Toll-like receptor pathway were proven to be involved in the occurrence of these diseases. Hub genes identified from PPI network, including DUSP6, BHLHE40, RASGRP1 and TAB2, were found to serve as potential therapeutic targets in COVID-19 with AKI and CKD. Common genes and pathways may play pathogenic roles in these three diseases mainly through the activation of immune inflammation. We constructed networks of transcription factor (TF)-gene, miRNA-gene and gene-disease interactions from the datasets. The key gene regulators influencing the progression of these three diseases and the various diseases from DEGs were further identified. We also predicted new drug targets based on these common DEGs and performed molecular docking and molecular dynamic (MD) simulations. Finally, the diagnostic model of COVID-19 was established based on these common DEGs. Taken together, the potential molecular and signaling pathways identified in this study may be the vital mechanisms by which SARS-CoV-2 infections affect renal function in patients. These findings are significant for the effective treatment of COVID-19 in patients with kidney diseases.